2019
DOI: 10.1016/j.psychres.2018.11.074
|View full text |Cite
|
Sign up to set email alerts
|

Schizotypal personality and semantic functioning: Revisiting category fluency effects in a subclinical sample

Abstract: Semantic disturbances have been proposed as a possible cause of formal thought disorder in schizophrenia. Fluency tasks, in which volunteers are asked to produce as many exemplars as they can for a given category during one minute, are usually applied to the assessment of semantic processing. However, studies associating fluency and proneness to psychosis have provided conflicting results so it is not clear whether these disturbances can be identified at subclinical stages. We conducted two experiments. In the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…The schizotypal group produced a similar number of words and employed comparable strategies and search cues to healthy controls. Consistent with these results, other studies using standard VFT paradigms have found that psychometric schizotypy was not associated with production of fewer words 24 , 29 , 30 or lower semantic coherence of responses. 23 However, some studies have found VFT performance deficits in particular subcategories of schizotypy, such as individuals with interpersonal 51 and paranoid 52 symptom clusters.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The schizotypal group produced a similar number of words and employed comparable strategies and search cues to healthy controls. Consistent with these results, other studies using standard VFT paradigms have found that psychometric schizotypy was not associated with production of fewer words 24 , 29 , 30 or lower semantic coherence of responses. 23 However, some studies have found VFT performance deficits in particular subcategories of schizotypy, such as individuals with interpersonal 51 and paranoid 52 symptom clusters.…”
Section: Discussionsupporting
confidence: 84%
“…One study found that schizotypy was associated with more atypical VFT responses, 29 whereas another study did not find this association. 30 Overall, while schizotypy shares the phenotype of odd speech (eg, metaphorical, illogical, stereotyped language) with schizophrenia, 26 standard VFT paradigms might not be sensitive to these linguistic irregularities. Evidence is accumulating that the addition of an affective or cognitive load may disproportionately impact the amount and organization of speech in individuals with schizotypal traits compared to healthy controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Crucially, in accordance with previous observations with schizophrenia patients (see Pomarol-Clotet et al, 2008 ), some authors argue that this mechanism could also underlie the presence of atypical speech patterns or ideas of reference associating unrelated events in schizotypal individuals ( Mohr et al, 2001 ; Pizzagalli, Lehmann & Brugger, 2001 ). Nevertheless, other studies have failed to obtain significant associations between the originality of fluency responses ( Hori et al, 2008 ; Rodríguez-Ferreiro & Aguilera, 2019 ) or semantic-based false memory rates ( Corlett et al, 2009 ; Kanemoto et al, 2013 ; Rodríguez-Ferreiro, Aguilera & Davies, 2020 ) and differences on schizotypal traits, so the reliability of these observations is unclear.…”
Section: Introductionmentioning
confidence: 97%
“…Atypical patterns of semantic activation in individuals with schizotypal personality have been hypothesized to underlie some of the most significant schizotypal symptoms, like thought disorder (Johnston et al, 2008), odd speech (Minor et al, 2010), delusion (Laws and Bhatt, 2005), or magical thinking (Saunders et al, 2012). Empirically, this proposal is based on previous findings associating schizotypy with semantic effects such as more original responses in semantic fluency tasks (Kiang and Kutas, 2005;Rodríguez-Ferreiro and Aguilera, 2019) or increased semantic priming (Moritz et al, 1999;Johnston et al, 2008), among others. Theoretically, this hypothesis relies on a conception of semantic memory as a network of interconnected nodes in which, when a given node is activated, semantic activation spreads to associated nodes, with stronger associates receiving higher activation levels than weaker ones (Collins and Loftus, 1975).…”
Section: Introductionmentioning
confidence: 99%